The Potential of The Entomopathogenic Fungus Beauveria Bassiana (bals) Vuillemin to Control Mealybugs Planococcus spp. Hemiptera: Pseudococcidae - Taupiq, Lukman; Sudantha, I Made; Sudharmawan, A. A. (Jurnal Biologi Tropis, 2024)
The mealybug insect pest planococcus spp. (Hemiptera: Pseudococcidae) attacks most plants, including food, horticultural, and plantation crops, which directly impacts reducing yields. Continuous control using pesticides made from synthetic chemicals harms environmental sustainability. The use of the entomopathogenic fungus Beauveria bassiana as a pest control for Planococcus spp. can be a long-term, environmentally friendly solution. The Beauveria bassiana fungus can kill all insect stages of various plant pests from all insect pest orders. The efficacy of beauveria bassiana is influenced by various types of enzymes from the secondary metabolites produced, namely: chitinase, protease, amylase, and lipase which function as degraders of the insect integument layer. Efficacy is also influenced by the production of toxins consisting of beauvericin, bassianin, bassiacridin, beauvericin, bassianolide, cyclosporine, oosporein, and tenellin which disrupt the nervous system and kill target insects. The results showed that the application of the Beauveria bassiana fungus was effective in reducing the population of the pest Planococcus spp. and reducing plant damage. The Beauveria bassiana mushroom is an alternative substitute for pesticides made from synthetic chemicals and is very prospective to be used as a biopesticide in controlling the pest Planococcus spp. which attacks agricultural plants and plantations.